2020
DOI: 10.4067/s0717-97072020000404953
|View full text |Cite
|
Sign up to set email alerts
|

CHEMICAL CHARACTERIZATION OF LIGNANS FROM Araucaria araucana A NATIVE CONIFER OF CHILE AND EVALUATION OF THEIR CYTOTOXICITY AND ANTIOXIDANT ACTIVITIES

Abstract: Araucaria araucana is a native conifer of Chile commonly called Araucaria. The knots of Araucaria are extremely hard wood and highly rot-resistant, they can be found in the forest decades after that the tree has dead and decomposed. Here we report the phytochemical characterization of different parts of the Araucaria as stemwood, branch and knots, founding a remarkable difference in the content of extractables in these parts, as well as the lignan composition, which is higher in knots than in branches or stemw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…It has been reported that other lignan similar to Eu, Sesamin, has showed neuroprotective effects involving anti-inflammatory paths [50,51]. We isolated Eu from Araucaria araucana, a native conifer from Chile that indigenous people have used as food and traditional medicine [41]. Eu did not show toxicity in the concentration range investigated (1-1000 nM), using a cellular viability assay (Supplementary Figure 1).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…It has been reported that other lignan similar to Eu, Sesamin, has showed neuroprotective effects involving anti-inflammatory paths [50,51]. We isolated Eu from Araucaria araucana, a native conifer from Chile that indigenous people have used as food and traditional medicine [41]. Eu did not show toxicity in the concentration range investigated (1-1000 nM), using a cellular viability assay (Supplementary Figure 1).…”
Section: Discussionmentioning
confidence: 90%
“…Soxhlet extraction was made with 2-5 g of sample placed in a cellulose thimble with acetone (250 mL) and refluxed for 12 h. The organic layer was filtered through a GV Durapore filter (0.22 m pore size, 13 mm diameter, Millipore, Bedford, MA, USA) and evaporated under reduced pressure, and dried in vacuum to give the extract. Subsequently, isolation of Eu (yield 1% w/w) was obtained after dissolve the extract in hot ethanol (70 • C) and kept in cold in 4 • C for 8 h. Eu was frozen at -20 • C until use with a 96-98% purity as previously described [41].…”
Section: Eudesmin Obtention and Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent contribution in the characterization of lignans from the A. araucana plant, growing in Chile over 2000 m, is due to Bravo-Arrepol [ 21 ]. The knots (picoyo) of this tree are made of extremely hard wood, and with respect to A. angustifolia knots enriched in lignans; the latter has not been well characterized.…”
Section: Lignans From Plants Of Different Speciesmentioning
confidence: 99%